2020
DOI: 10.48550/arxiv.2005.03431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global Hydromagnetic Simulations of Protoplanetary Disks with Stellar Irradiation and Simplified Thermochemistry

Oliver Gressel,
Jon P. Ramsey,
Christian Brinch
et al.

Abstract: Outflows driven by large-scale magnetic fields likely play an important role in the evolution and dispersal of protoplanetary disks, and in setting the conditions for planet formation. We extend our 2-D axisymmetric non-ideal MHD model of these outflows by incorporating radiative transfer and simplified thermochemistry, with the twin aims of exploring how heating influences wind launching, and illustrating how such models can be tested through observations of diagnostic spectral lines. Our model disks launch m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 125 publications
(167 reference statements)
0
14
0
Order By: Relevance
“…Recent global non-ideal MHD simulations of magnetised disks, including more comprehensive disk microphysics and evolving both hemispheres, have confirmed these early results and shown that pronounced asymmetries between the lower and upper disk halves of the disk can develop and launch asymmetric outflows which persist over timescales of at least 1000 times the orbital period at the inner disk radius (Béthune et al 2017;Bai 2017;Gressel et al 2020;Riols et al 2020). However, most of these recent simulations do not currently include the very central regions of the disk (r ≤ 1 au) from which the high-velocity jets are launched.…”
Section: The Origin Of the Velocity Asymmetrymentioning
confidence: 80%
“…Recent global non-ideal MHD simulations of magnetised disks, including more comprehensive disk microphysics and evolving both hemispheres, have confirmed these early results and shown that pronounced asymmetries between the lower and upper disk halves of the disk can develop and launch asymmetric outflows which persist over timescales of at least 1000 times the orbital period at the inner disk radius (Béthune et al 2017;Bai 2017;Gressel et al 2020;Riols et al 2020). However, most of these recent simulations do not currently include the very central regions of the disk (r ≤ 1 au) from which the high-velocity jets are launched.…”
Section: The Origin Of the Velocity Asymmetrymentioning
confidence: 80%
“…Expanding the set of molecular diagnostics for the inner winds, as well as the sample of disks with detections, to date restricted to suggestive evidence only in a handful of disks, will be important to better constrain wind mass loss rates. Disk wind models that properly couple thermodynamics and hydrodynamics are being developed (e.g., Gressel et al 2020) The sources CS Cha, MP Mus, T Cha, TY CrA, T CrA, V4046 Sgr, and VW Cha have very noisy or no published high-resolution optical spectra. For all of them except TY CrA, we retrieved from the ESO archive 9 the highest signalto-noise UVES spectra (R∼45,000) available 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these nonideal MHD simulations persistently predict the presence of disk winds, defined as outflowing gas from a few scale heights above the disk midplane. The simulated winds extract enough angular momentum to drive accretion at the observed rates (e.g., Gressel et al 2015;Bai 2016;Gressel et al 2020). These outer winds (beyond a few au out to tens of au in some models), combined with the closer-in winds likely responsible for outflowing gas at hundreds of km/s (hereafter jets, e.g., Frank et al 2014), could drive disk evolution with important implications for planet formation and migration (e.g., Ogihara et al 2018;Kimmig et al 2020).…”
Section: Introductionmentioning
confidence: 91%
“…The FLD method is well-suited for radiation transport in optically-thick media but is not adapted to strongly anisotropic radiation fields. The particular treatment of the stellar radiation, also called irradiation, has been improved later on to track the higher-energy stellar photons and compute accurately the opacity during their first interaction with the ambient medium (Kuiper et al 2010b, Flock et al 2013, Ramsey & Dullemond 2015, Rosen et al 2017, Mignon-Risse et al 2020,Gressel et al 2020, Fuksman et al 2020.…”
Section: Introductionmentioning
confidence: 99%